Analysis of death in major trauma: value of prompt post mortem computed tomography (pmCT) in comparison to office hour autopsy. Issue 1 (December 2016) - Schmitt-Sody, MArkus; Kurz, Stefanie; REiser, MAximilian; Kanz, Karl; Kirchhoff, Chlodwig; Peschel, Oliver; Kirchhoff, Sonja
Abstract Background To analyze diagnostic accuracy of prompt post mortem Computed Tomography (pmCT) in determining causes of death in patients who died during trauma room management and to compare the results to gold standard autopsy during office hours. Methods Multiple injured patients who died during trauma room care were enrolled. PmCT was performed immediately followed by autopsy during office hours. PmCT and autopsy were analyzed primarily regarding pmCT ability to find causes of death and secondarily to define exact causes of death including accurate anatomic localizations. For the secondary analysis data was divided in group-I with equal results of pmCT and autopsy, group-II with autopsy providing superior results and group-III with pmCT providing superior information contributing to but not majorly causing death. Results Seventeen multiple trauma patients were enrolled. Since multiple trauma patients were enrolled more injuries than patients are provided. Eight patients sustained deadly head injuries (47.1 %), 11 chest (64.7 %), 4 skeletal system (23.5 %) injuries and one patient drowned (5.8 %). Primary analysis revealed in 16/17 patients (94.1 %) causes of death in accordance with autopsy. Secondary analysis revealed in 9/17 cases (group-I) good agreement of autopsy and pmCT. In seven cases autopsy provided superior results (group-II) whereas in 1 case pmCT found more information (group-III). Discussion The presented work studied the diagnostic value of pmCT in defining causes of death in comparison to standard autopsy. Primary analysis revealed that in 94.1% of cases pmCT was able to define causes of death even if only indirect signs were present. Secondary analysis showed that pmCT and autopsy showed equal results regarding causes of death in 52.9%. Conclusions PmCT is useful in traumatic death allowing for an immediate identification of causes of death and providing detailed information on bony lesions, brain injuries and gas formations. It is advisable to conduct pmCT especially in cases without consent to autopsy to gain information about possible causes of death and to rule out possible clinical errors.